PENYELESAIAN PERMOHONAN IZIN POLIGAMI DI PENGADILAN AGAMA DALAM KAITANNYA DENGAN KEWENANGAN HAKIM DALAM MENJATUHKAN PUTUSAN - Devianty Fitri; Yussy A Mannas (ADHAPER: Jurnal Hukum Acara Perdata, 2018)
Polygamy is allowed only for those who their law and religion allowing a husband to have more than a wife. Such provision has been stated in general elucidation of Marriage Law at point 4c states that “This Law encourages monogamy. Only if requested by concerned parties, under their law and religion of the concerned parties, which allowing a husband to have more than a wife.” The word “law” in general elucidation of Marriage Law at point 4c refers to the marriage law of the husband. The Judge of Religious Court may have competency to consider any reasons and requirements of request for polygamy. The Judge of Religious Court shall try the case and render its judgment in accordance to the prevailing laws, Al Qur’an, Al Hadits, and the opinion of Islamic scholars. The judgment must have clear and sufﬁ  cient consideration, in which the judge may base its verdict. Article 62(1) of Law No. 7 of 1989 concerning Religious Court provides that all ex parte decisions and judgments rendered by the court shall contain sufﬁcient consideration and refer to certain rules of the prevailing laws both written or unwritten regulation.